PEMASANGAN PENERANGAN JALAN UMUM (PJU) BERBASIS SEL SURYA DI DUSUN SANGGRAHAN, DESA MUNTUK, KECAMATAN DLINGO, KABUPATEN BANTUL - Harry Prabowo; Arbye S; Wahri Sunanda (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2023)
Sanggrahan 1 Hamlet is one of the areas in Muntuk Village, Dlingo District, Bantul Regency. One of the obstacles faced by the Sanggrahan 1 hamlet community is limited access to street lighting at several points in their area, resulting in limited community activities and mobility. Through community service activities which are the implementation of the Tri Dharma of University, the Department of Electrical Engineering and Information Technology (DTETI), Faculty of Engineering, Gadjah Mada University, initiated a program to install PJUTS of LED lights at 12 points in the area. In general, this activity uses a participatory and collaborative approach, where the village government, community, and also universities work together to solve problems that occur in social life. The installation of PJUTS must have a significant impact. Better street lighting opens up new opportunities for community activities at night, improve safety, and support mobility. The installation of PJUTS also increased productivity and economic progress in Dusun Sanggrahan 1